EVOLUSI FUNGSI GEDUNG MUSEUM SULTAN MAHMUD BADARUDDIN II DI PALEMBANG SEBAGAI SIMBOL PELESTARIAN BUDAYA - Fadina Nayla; Aliyah Nazahah Santosa; Charina Haris; Dzikrila Bunga Cahyani; Olga Maharani; Amrina Rosada; Listen Prima; Sri Lilianti Komariah (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: The Sultan Mahmud Badaruddin II Museum building is a historic structure in the city of Palembang that has undergone significant functional transformation since the nineteenth century. The building was constructed by the Dutch colonial government in 1823–1824 on the former site of the Palembang Sultanate palace, which had been demolished following the dissolution of the sultanate. Initially, the structure functioned as the official residence of the Dutch Resident and as the administrative office of colonial governance in Palembang. This study aimed to analyse the evolution of the building’s function and to examine the shift in its symbolic meaning from a centre of colonial authority to a symbol of cultural preservation. A qualitative method with historical and architectural approaches was employed. Data were collected through direct observation, interviews with museum administrators, and relevant literature review. The data were analysed descriptively and comparatively through stages of data reduction, historical classification, interpretation, and source triangulation. The findings indicate that the building evolves through several stages, from a colonial administrative centre and a military base during the Japanese occupation to a public museum established in 1984. Its tropical architectural adaptation enables the structure to endure and to be reused without losing its authenticity. The transformation demonstrates that the building now functions as a symbol of cultural preservation and the reinforcement of Palembang’s local identity. Keyword: SMB II Museum, building evolution, cultural preservation, colonial architecture. Abstrak: Gedung Museum Sultan Mahmud Badaruddin II di Kota Palembang merupakan bangunan bersejarah yang mengalami perubahan fungsi signifikan sejak abad ke-19. Bangunan yang didirikan oleh pemerintah kolonial Belanda pada tahun 1823–1824 di atas bekas Keraton Palembang Darussalam ini awalnya berfungsi sebagai kediaman residen sekaligus pusat administrasi kolonial. Penelitian ini bertujuan untuk menganalisis evolusi fungsi bangunan serta mengkaji pergeseran makna simboliknya. Metode yang digunakan adalah kualitatif dengan pendekatan historis dan arsitektural melalui observasi, wawancara, dan studi literatur, kemudian dianalisis secara deskriptif komparatif. Hasil penelitian menunjukkan bahwa bangunan mengalami perubahan fungsi bertahap, mulai dari pusat administrasi kolonial, basis militer pada masa pendudukan Jepang, aset pemerintahan pascakemerdekaan, hingga menjadi museum sejak tahun 1984. Selain itu, karakter arsitektur kolonial yang adaptif terhadap iklim tropis memungkinkan bangunan tetap bertahan dan dialihfungsikan tanpa menghilangkan keaslian bentuknya. Transformasi ini menunjukkan pergeseran makna simbolik dari representasi kekuasaan kolonial menjadi simbol pelestarian sejarah dan identitas lokal masyarakat Palembang. Kata Kunci: Museum SMB II, evolusi bangunan, pelestarian budaya, arsitektur kolonial.